Väitöskirja harmaahomeen biologisesta torjunnasta metsätaimitarhoilla - Poteri, Marja (Metsäntutkimuslaitos, 2005)
Selostus julkaisuista: Capieau, Kristof. 2004. Biological control of grey mold in Swedish forest nurseries. Silvestria 325. Väitöskirja. Capieau Kristof, Stenlid Jan & Stenström Elna. 2004. Potential for biological control of Botrytis cinerea in Pinus sylvestris seedlings. Scandinavian Journal of Forest Research 19: 312-319.
Julkaisusatoa